AKTIVITAS PENGHAMBATAN ENZIM PROTEASE 6LU7 VIRUS SARS-COV-2 OLEH SENYAWA ALKALOID DARI ATTARASA (Litsea cubeba (Lour.)Pers.) SECARA IN-SILICO - Jon Kenedy Marpaung; Melisa Rekayana Tambuan (Jurnal Farmanesia, 2020)
Attarasa (Litsea cubeba (Lour.) Pers.) is a mountain plant known as "Mountain pepper" or "Mountain Pepper". This plant contains alkaloids, such as Oblongine; Actinodaphine; Isoboldine; Cassameridine; Coclaurine; Corydine; Corytuberine; Dicentrine; Laurotetanine; Lindcarpine; Isocorydine; Isodomesticine; Juziphine; N-Methylcoclaurine; N-Methyllaurotetanine; N-Methyllindcarpine; Norcorydine; Norisoboldine; Norisocorydine; Xanthoplanine. Alkaloids in Attarasa (Litsea cubeba (Lour.) Pers.) have properties such as antimicrobials. This study aimed to determine the inhibition of the protease enzyme 6LU7 of the SARS-CoV-2 virus by an alkaloid compound from Attarasa (Litsea cubeba (Lour.) Pers.) by using the in silico tethering method. The in silico tethering process is carried out using the PLANTS program and visualized using the MOE2008 program. The protease enzyme was downloaded via the Protein Data Bank (PDB) with the code 6LU7. Two- and three-dimensional models are generated using the Marvin Sketch program. The resulting docking value is evaluated as a result of the docking process. The results of this study indicate that the binding of alkaloid compounds from Attarasa (Litsea cubeba (Lour.) Pers.) to 6LU7 expression gave valid results in silico. The compound N-Methylcoclaurine, Coclaurine, and Laurotetanin inhibited the protease enzyme 6LU7 with the best score close to the comparative value of Lopinavir and Remdesivir and produced 7 amino acid residues that were bound to each other, namely val_114, val_13, leu_115, phe_150, gly_140, val_140, and ser_147.